Teacher Commitment in Motivating Students as a Form of Performance to Improve Achievement and Quality of Graduates at Madarasah Aliyah - Sutijah, Sutijah; Warisno, Andi; Asrori, Achmad; Abun, A. Rifa’i (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to deeply understand and analyze teachers' commitment in motivating students as a form of professional performance in improving learning achievement and the quality of graduates at Ma'arif Islamic Senior High School in Central Lampung Regency. This research employs a qualitative approach, utilizing data collection techniques such as in-depth interviews, direct observation, documentation, and literature study to obtain comprehensive and contextual data. The data were analyzed using the interactive model of Miles and Huberman, which involves data reduction, data display, and conclusion drawing carried out continuously until data saturation was achieved. The findings reveal that teachers' commitment is generally categorized as good, as reflected in their ability to plan, implement, and evaluate learning regularly. Teachers also actively function as motivators by applying various strategies, including personal approaches, interactive and student-centered learning methods, as well as the use of rewards and educative punishments. These efforts have a positive impact on increasing student participation, motivation, and overall academic performance. Furthermore, teacher commitment contributes significantly to improving the quality of graduates, not only in terms of academic achievement but also in character development, such as discipline, responsibility, and self-confidence. In conclusion, teacher commitment plays a crucial role in enhancing learning quality and graduate outcomes, although it remains influenced by external factors such as limited educational facilities and students' socio-economic backgrounds.